Studies in Honour of Clifford Edmund Bosworth, Volume I : Hunter of the East: Arabic and Semitic Studies - Netton, Ian, (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
Professor C.E. Bosworth FBA is a Middle East historian of world stature. In this volume his friends and colleagues come together to honour his 70th birthday. The diversity of these essays reflects the diversity and depth of Professor Bosworth's own interests. Ranging through the five areas of Literature, Language, History, Law, and Art and Epigraphy, this volume embraces the ancient, the medieval and the modern, covering topics as diverse as the Maqāma genre, the significance of wooden weapons in al-Mukhtār's revolt and nineteenth century exchanges in Himyaritic inscriptions. The volume illustrates the vibrancy and dynamism of modern scholarship in the field of Arabic and Semitic Studies.